GLOBAL ENGLISH: GRAMMATICAL DIFFERENCES AMONG REGIONAL VARIETIES (BRITISH, AMERICAN, AUSTRALIAN, AND INDIAN ENGLISH) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides an in-depth analysis of grammatical differences among four major varieties of English: British, American, Australian, and Indian English. Utilizing a qualitative comparative research methodology, it draws upon prominent linguistic corpora and academic sources to explore variations in verb tense usage, modal verbs, prepositional structures, auxiliary usage, article deployment, and question formation. The study further discusses the socio-cultural and historical factors that have contributed to the divergence of these varieties, emphasizing the need for inclusive pedagogical approaches in English language education. By understanding these regional grammatical norms, learners and educators can better navigate and respect linguistic diversity in global communication. This research contributes to the broader discussion on World Englishes, fostering awareness and flexibility in academic and professional settings.